Radio and electronics cookbook - Brown, George, 1941-; Radio Society of Great Britain. (Boston, 2001)
The RSGB Radio and Electronics Cookbook is a unique collection of electronics projects, ideal for all electronics enthusiasts and experimenters. The simple step-by-step instructions also make this book ideal for amateurs seeking to build up their electronics skills and knowledge. The projects draw on the massive enthusiasm and design know-how of the RSGB, the UK's leading federation of radio amateurs. Only a basic acquaintance with electronics construction is assumed, with clear step-by-step instructions and numerous illustrations supplied throughout. The projects are also supported with featu.